Ecologia do movimento e dinâmica espaço-temporal da onça-pintada (Panthera onca) no Pantanal sul do Brasil - Kanda, Claudia Zukeran [UNESP] (2015)
All living things interact with other conspecifics or with other species. The presence of conspecific can influence individual movement patterns and determine individual's space use. The space use emerges from individual movement process, and the decisions for when and where to move are related by habitat selection that enhance the location of resources for increase your fitness to growth, survival and reproduction. Mammals restrict its movements in familiar habitats and this selection can be associated to their circadian rhythm. In carnivores mammals the presence of near conspecifics can also be an important factor in the space use, as an attraction impulse for reproduction or a repulse action to minimize direct interference to get resources. This project aimed to analyze the determining factors in space use by jaguars (Panthera onca) in the Pantanal of Brazil. Conditional logistic regression was applied for adjusted Step Selection Functions (SSF) model to understand how and which factors affect space use. Homing behavior was estimated by selection strength in function for distance from the center of individual home range and habitat selection changing over circadian cycle was estimated by selection strength in function for day hours. The conspecific influence on movement was characterized using a set of data acquired simultaneously from animals tracking and individuals with contiguous home range. In addition, the presence of conspecific responses was estimated by the selection strength of nearest individual for movement at each steps. These results indicate that the space use by organisms is predicted by habitat selection along the circadian cycle, differences in the homing behavior between sexes and by spatial-temporal dynamic ...